Health Professional Education Alarming Crisis Knocking Our Doors - Khanal, Dharma Prasad (Journal of Manmohan Memorial Institute of Health Sciences, 2023)
The education of health professionals was creeping before multiparty political system in 1990 and substantially changed after this political event in Nepal. Free market economy opens the avenue of privatization of different sector of business and education sector only was not an exception. Several transformative developments have happened in education sector but all of them were donor driven that is becoming unfortunate for the country. In the period from 1990 to 2015 so many policy reformations occur for the implementation of free market economic concept that foster mushrooming of private educational institutions especially in class 12 level (we denote it as plus two in Nepal) followed by flooding affiliations of different universities for private colleges and they are likely to have a long-term effect on education system including health-professional education (HPE). The quality of HPE imparted directly affects the people’s health and it is thus very important to focus our attention towards it. But there was critical imbalance between the education and business. Moreover, the curricula of HPE of many universities is outdated and the topic stays within the confines of the four walls of the classroom and has no relevance in their daily lives although these are matters of routine healthcare.